Application of DIgSILENT POWERFACTORY software for modeling of industrial network relay protection system - Sučević, Nikola J.; Milošević, Dejan (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
This paper presents modeling of industrial network relay protection system using DIgSILENT PowerFactory software. The basis for the model of protection system is a model of a single substation in an industrial network for the purposes of load flow and short circuit analysis. The paper presents a methodology of modeling selected protective function of the relay protection system for analyzed substation. The procedure for modeling of measuring transformers, protective devices of 6 kV asynchronous motors and 6/0,4 kV/kV transformers powered from analyzed substation, as well as protection in the bus coupler and busbar protection. Keywords: relay protection, DIgSILENT PowerFactory, industrial network